Rapid extraction and separation of indium(III) with a high molecular weight amine - Shilmkar, T. N.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Indian Journal of Chemical Technology, 2008)
The liquid-liquid extraction of indium(III) from sodium succinate media using n-octylaniline in toluene as an extractant was studied. Quantitative extraction of indium(III) was observed in the range of 0.004-0.0075 M sodium succinate at pH 3.8-6.0 with 4% n-octylaniline in toluene. Indium(III) was completely stripped from the metal loaded organic phase of the extractant with water and determined complexometrically. The stoichiometry of the extracted species was determined on the basis of;slope analysis. The extraction was found to proceed by a ion-pair mechanism with the extracted species being [RNH3+In(succinate)(2)(-)](org). Separation of indium(III) was carried out from some associated metals like Tl(I), Mg(II), Ni(II), Cu(II), Zn(II),. Cd(II), Hg(II), Pb(II), GC(IV), Sb(III), Bi(III). The selectivity of the extraction of indium(III) can also be achieved by use of a suitable masking agent for estimation and determination from the synthetic mixture corresponding to alloy to show the practical utility of the extractant.
Keywords: Indium(III); n-octylaniline; Separation; solvent extraction; succinate

Solvent extraction of trivalent indium from succinate solution by 2-octylaminopyridine in chloroform - Mahamuni, Sandip V.; Kolekar, S. S.; Wadgaonkar, P. P.; Anuse, Mansing A. (Journal of the Iranian Chemical Society, 2009)
Extraction processes of indium(III) with 2-octylaminopyridine (2-OAP) from media of various complexing ability, succinate and salicylate, in chloroform have been elucidated. The ion-pair complex has also quantitative extraction in xylene and 1,2-dichloroethane. Indium(III) from organic phase was stripped with 1.0 M hydrochloric acid and determined complexometrically with EDTA. The stoichiometry of the extracted species was found out on the basis of slope analysis. The extraction of indium(III) proceeds by an anion exchange mechanism and the extracted species is [RR'NH(2)(+)In(succinate)(2)(-)]((org)). Temperature dependence of the extraction equilibrium constant was also examined to estimate the apparent thermodynamic functions (Delta H, Delta G and Delta S) for extraction reaction. It is possible to separate indium(III) from Zn(II), Cd(II), Pb(II), Hg(II), Bi(III), Tl(I), Tl(III), Ga(III), Al(III), Te(IV), Se(IV), Sb(III), Fe(III) and Sn(IV). The method is simple, rapid and reproducible and can be used to determine the indium from samples like alloys.
Keywords: 2-OAP; Binary separations; Indium(III); liquid-liquid extraction; Sodium succinate